2021
DOI: 10.1155/2021/6684680
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility Patterns in Neisseria gonorrhoeae Isolated from South African Pregnant Women

Abstract: Background. Neisseria gonorrhoeae, a sexually transmitted infection, is associated with adverse pregnancy and neonatal outcomes. Emerging resistance towards various antibiotics has been observed globally. However, there is a lack of data on antimicrobial susceptibility patterns in N. gonorrhoeae isolated from pregnant women in our setting. This study fills in this gap in the literature. Methods. The study population included pregnant women, recruited from the antenatal clinic of the King Edward VIII hospital (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This is comparable to studies conducted in Mekelle, Ethiopia (10.04%) [ 30 ], in Italy (7.4%) [ 31 ]; Iran (7.2%) [ 32 ]; South Africa (6.8%) [ 33 ]; Swaziland (6.0%) [ 12 ]; Jimma, Ethiopia (9.4%) [ 29 ], and Gambella, Ethiopia (5.0%) [ 34 ]. However, it was higher than studies reported from Ethiopia: Hawassa (3.3%) [ 35 ]; Bahir dar (4.7%) [ 36 ]; and Hawassa again (4.3%) [ 37 ]; (1.6%) in Kenya [ 38 ]; (1.8%) in Gambia [ 39 ]; (1.9%) in South Africa [ 40 ]; and 1.0% in Brazil [ 41 ]. On the other hand, our result was lower than the studies from Addis Ababa, Ethiopia (11.4%) [ 42 ]; and Ghana (28.3%) [ 43 ].…”
Section: Discussionmentioning
confidence: 74%
“…This is comparable to studies conducted in Mekelle, Ethiopia (10.04%) [ 30 ], in Italy (7.4%) [ 31 ]; Iran (7.2%) [ 32 ]; South Africa (6.8%) [ 33 ]; Swaziland (6.0%) [ 12 ]; Jimma, Ethiopia (9.4%) [ 29 ], and Gambella, Ethiopia (5.0%) [ 34 ]. However, it was higher than studies reported from Ethiopia: Hawassa (3.3%) [ 35 ]; Bahir dar (4.7%) [ 36 ]; and Hawassa again (4.3%) [ 37 ]; (1.6%) in Kenya [ 38 ]; (1.8%) in Gambia [ 39 ]; (1.9%) in South Africa [ 40 ]; and 1.0% in Brazil [ 41 ]. On the other hand, our result was lower than the studies from Addis Ababa, Ethiopia (11.4%) [ 42 ]; and Ghana (28.3%) [ 43 ].…”
Section: Discussionmentioning
confidence: 74%
“…In Washington State in 2014, the incidence of gonorrhea infection in women ages 15-24 was 273 cases per 100,000 women and this has been rising in the past five year [7] Neisseria gonorrhoeae is A global STI surveillance in 2018 was conducted by the World Health Organization (WHO) and revealed an estimated 87 million new gonorrhoea infections globally during 2016, with an incidence of 20 cases per 1000 population in women . A study conducted exclusively on pregnant women reported a prevalence of 1.3% for N. gonorrhoeae [8] One of the most important reasons for infertility is tubular factor related to untreated sexually transmitted diseases that one of these causative agents is Neisseria gonorrhea [9]. N.gonorrhea is major causes of maternal and neonatal morbidity and mortality in developing countries [10].…”
Section: Neisseria Gonorrheamentioning
confidence: 99%